2011
DOI: 10.1111/j.1525-1446.2010.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using the Omaha System to Represent Public Health Nurse Manager Interventions

Abstract: Nursing practice differed between the 2 knowledge domains of public health family home visiting nursing and public health nursing management. Standardized nursing terminologies have the potential to represent, describe, and quantify nurse manager interventions for future evaluation and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…[36][37][38][39][40] Outcomes evaluation showed statistically significant improvements in knowledge, behavior, and status for most problems during the time of the student clinical practicum. This is consistent with previous studies with the elderly in Turkey 21,28 and in other countries.…”
Section: Discussionmentioning
confidence: 98%
“…[36][37][38][39][40] Outcomes evaluation showed statistically significant improvements in knowledge, behavior, and status for most problems during the time of the student clinical practicum. This is consistent with previous studies with the elderly in Turkey 21,28 and in other countries.…”
Section: Discussionmentioning
confidence: 98%
“…The Omaha System as a standardized terminology can be used to guide and document nursing care. Several studies have demonstrated the suitability of the Omaha System in primary care settings for documenting nursing activities (Altiner, Secginli, Mathiason, & Monsen, 2019;Baisch, 2012;Erdogan et al, 2013;Monsen & Newsom, 2011;Olsen, Thorson, Baisch, & Monsen, 2017). Although use of the Omaha System is currently not required in FHCs, it has been translated and tested in Turkish (Erdogan & Esin, 2006) and has been used in research in family health, school health, and home health settings (Aktas, Yilmaz, Kaplan, & Cankiri, 2016;Altiner et al, 2019;Erdogan et al, 2013;Kerr et al, 2015Kerr et al, , 2019.…”
Section: The Omaha Systemmentioning
confidence: 99%
“…In addition, it is known that the number of problems families have accrues to their detriment (Barnard, 1998; Olds, 2002). Furthermore, previous studies have shown that lower baseline knowledge scores are associated with poorer outcomes (Monsen, 2002). To date, no risk indices based on Omaha System data have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%